2021
DOI: 10.3390/cells10071827
|View full text |Cite
|
Sign up to set email alerts
|

Mitotherapy: Unraveling a Promising Treatment for Disorders of the Central Nervous System and Other Systemic Conditions

Abstract: Mitochondria are key players of aerobic respiration and the production of adenosine triphosphate and constitute the energetic core of eukaryotic cells. Furthermore, cells rely upon mitochondria homeostasis, the disruption of which is reported in pathological processes such as liver hepatotoxicity, cancer, muscular dystrophy, chronic inflammation, as well as in neurological conditions including Alzheimer’s disease, schizophrenia, depression, ischemia and glaucoma. In addition to the well-known spontaneous cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Heterogeneity, mutations, and deletions in mtDNA have been implicated in a wide range of diseases, frequently involving neurodegenerative/neuromuscular pathologies ( Burté et al, 2015 ; Lightowlers et al, 2015 ; Area-Gomez et al, 2019 ; Monzio Compagnoni et al, 2020 ; Ng et al, 2021 ). It is plausible that mitochondrial therapy, by stimulation of HMT or by mitochondrial transplantation, may be effective in alleviating pathologies, with neurodegenerative or cardiovascular diseases being “hot” candidates for the emerging therapeutic modality ( Emani and McCully, 2018 ; Picard et al, 2016 ; Caicedo et al, 2017 ; Chang et al, 2019 ; McCully et al, 2017 ; Nascimento-Dos-Santos et al, 2021 ; Gorman et al, 2018 ). Mitochondrial transplantation has been used to replace faulty maternal mitochondrial genes ( Gorman et al, 2018 ; Jacoby et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity, mutations, and deletions in mtDNA have been implicated in a wide range of diseases, frequently involving neurodegenerative/neuromuscular pathologies ( Burté et al, 2015 ; Lightowlers et al, 2015 ; Area-Gomez et al, 2019 ; Monzio Compagnoni et al, 2020 ; Ng et al, 2021 ). It is plausible that mitochondrial therapy, by stimulation of HMT or by mitochondrial transplantation, may be effective in alleviating pathologies, with neurodegenerative or cardiovascular diseases being “hot” candidates for the emerging therapeutic modality ( Emani and McCully, 2018 ; Picard et al, 2016 ; Caicedo et al, 2017 ; Chang et al, 2019 ; McCully et al, 2017 ; Nascimento-Dos-Santos et al, 2021 ; Gorman et al, 2018 ). Mitochondrial transplantation has been used to replace faulty maternal mitochondrial genes ( Gorman et al, 2018 ; Jacoby et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In most studies, mitotherapy has shown positive results in various diseases and conditions, which can be promising from a therapeutic point of vision. 13,16,31,32 In the testing of chemical substances, human lymphocytes are considered one of the important systems. As primary cells, they play a role in the initiation and progression of hematological related malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…We know that mitochondria play an important part in cell life and death decisions; mitochondria can cause cell death in a variety of ways: by interfering with their own electron transport and energy metabolism, initiating the mitochondrial permeability transition, and releasing and/or activating apoptosis-mediating proteins. All of these pathways may assist in explaining how mitochondrial abnormalities lead to neuronal death or malfunction in ischemia/reperfusion injury, as well as in human degenerative disorders such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis, and Huntington’s disease [ 119 ]. Furthermore, the use of bioactive substances in mitotherapy will significantly reduce the negative impact of ROS production and cell viability [ 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%